Transformed Testicular Teratoma to Embryonic-Type Neuroectodermal Tumor With Metastasis to Mediastinum - Alanna Siegenthaler MD; Stephanie Niforatos MD; Taylor Loon MBBCh; Amy Brady DO; Michael Sandhu MD; Oleksandr Kravtsov MD; Komal Akhtar MD (SAGE Publishing, 2023)
Testicular teratomas may present in both prepubertal and adult men; however, the prognosis differs greatly between these 2 populations. In children, teratomas (prepubertal type) most often occur before the age of 4, are generally seen in their pure form, and behave in a benign fashion. In adults (postpubertal type), teratomas are usually part of a mixed germ cell tumor, and they have the potential to be found at metastatic sites, especially following chemotherapy for non-teratomatous germ cell tumor. Analyses of metastases from germ cell tumors and teratomas from the same patient have demonstrated a high degree of concordance in the observed genetic abnormalities. In rare cases, testicular teratoma can transform into a malignant germ cell tumor. One such type of transformation is into a primitive neuroectodermal tumor. These tumors are malignant and often metastasize to the retroperitoneum but may also metastasize to other sites. A multimodal treatment approach is needed, including surgery and adjuvant chemotherapy. We describe a rare case of malignant transformation of a testicular teratoma into a primitive neuroectodermal tumor with metastasis to the mediastinum. The patient was treated with radical orchiectomy, retroperitoneal lymph node dissection, and adjuvant vincristine, adriamycin, and cyclofosfamide alternating with ifosfamide and etoposide (VAC/IE therapy).